How to tackle health literacy problems in chronic kidney disease patients? A systematic review to identify promising intervention targets and strategies. Issue 7 (22nd December 2020) - Boonstra, Marco D; Reijneveld, Sijmen A; Foitzik, Elisabeth M; Westerhuis, Ralf; Navis, Gerjan; de Winter, Andrea F
Abstract: Background: Limited health literacy (LHL) is associated with multiple adverse health outcomes in chronic kidney disease (CKD). Interventions are needed to improve this situation, but evidence on intervention targets and strategies is lacking. This systematic review aims to identify potential targets and strategies by summarizing the evidence on: (i) patient- and system-level factors potentially mediating the relation between LHL and health outcomes; and (ii) the effectiveness of health literacy interventions customized to CKD patients. Methods: We performed a systematic review of peer-reviewed research articles in Medline, Embase and Web of Science, 2009–19. We assessed the quality of the studies and conducted a best-evidence synthesis. Results: We identified 860 publications and included 48 studies. Most studies were of low quality ( n = 26) and focused on dialysis and transplantation ( n = 38). We found strong evidence for an association of LHL with smoking and having a suboptimal transplantation process. Evidence was weak for associations between LHL and a variety of factors related to self-care management ( n = 25), utilization of care ( n = 23), patient–provider interaction ( n = 8) and social context ( n = 5). Six interventions were aimed at improving knowledge, decision-making and health behaviours, but evidence for their effectiveness was weak. Conclusions: Study heterogeneity, low quality and focus on kidney failure largely impede the identification of intervention targets and strategies for LHL. More and higher quality studies in earlier CKD stages are needed to unravel how LHL leads to worse health outcomes, and to identify targets and strategies to prevent disease deterioration. Healthcare organizations need to develop and evaluate efforts to support LHL patients.